Optimum Tariffs and Retaliation - Johnson, Harry G. (Review of Economic Studies, 1953)
Journal Article Optimum Tariffs and Retaliation Get access Harry G. Johnson Harry G. Johnson Cambridge Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 21, Issue 2, 1953, Pages 142–153, https://doi.org/10.2307/2296006 Published: 01 January 1953